Effect of Co-inhabiting Coagulase Negative Staphylococci on S. aureus agr Quorum Sensing, Host Factor Binding, and Biofilm Formation - Peng, Pai; Baldry, Mara; Gless, Bengt H.; Bojer, Martin S.; Espinosa-Gongora, Carmen; Baig, Sharmin J.; Andersen, Paal S.; Olsen, Christian A.; Ingmer, Hanne (Frontiers in Microbiology, 2019)
Staphylococcus aureus is a commensal colonizer of both humans and animals, but also an opportunistic pathogen responsible for a multitude of diseases. In recent years colonization of pigs by methicillin resistant S. aureus has become a problem with increasing numbers of humans being infected by livestock strains. In S. aureus colonization and virulence factor expression is controlled by the agr quorum sensing system, which responds to and is activated by self-generated, autoinducing peptides (AIPs). AIPs are also produced by coagulase negative staphylococci (CoNS) commonly found as commensals in both humans and animals, and interestingly, some of these inhibit S. aureus agr activity. Here we have addressed if cross-communication occurs between S. aureus and CoNS strains isolated from pig nares, and if so, how properties such as host factor binding and biofilm formation are affected. From 25 pig nasal swabs we obtained 54 staphylococcal CoNS isolates belonging to 8 different species. Of these, none were able to induce S. aureus agr as monitored by reporter gene fusions to agr regulated genes but a number of agr-inhibiting species were identified including S. hyicus, S. simulans, S. arlettae, S. lentus and S. chromogenes. After establishing that the inhibitory activity was mediated via AgrC, the receptor of AIPs, we synthesized selective AIPs to explore their effect on adhesion of S. aureus to fibronectin, a host factor involved in S. aureus colonization. Here we found that in the presence of CoNS AIPs, adhesion of S. aureus was enhanced for strain 8325-4 but not for a livestock-associated strain or strains isolated in this study. When individual CoNS strains were co-cultured together with S. aureus we observed variable degree of biofilm formation which did not correlate with agr interactions. Our results show that multiple CoNS species can be isolated from pig nares and that the majority of these produce AIPs that inhibit S. aureus agr. The consequences of this interaction for S. aureus colonization remain obscure but for some S. aureus strains it may lead to enhanced binding to host factors.